2020
DOI: 10.4997/jrcpe.2020.213
|View full text |Cite
|
Sign up to set email alerts
|

Microangiopathic Haemolytic Anaemia and Thrombocytopenia Due to Combined Vitamin B12 and Folate Deficiency Masquerading as Thrombotic Thrombocytopenic Purpura

Abstract: Vitamin B12 defi ciency and folate defi ciency are common causes of macrocytic anaemia and both are important for many cellular processes. These defi ciencies could be due to inadequate dietary intake, impaired absorption or drug ingestion. We present an interesting case of pancytopenia with microangiopathic haemolytic anaemia (MAHA) and intracranial bleeding (ICB) due to combined vitamin B12 and folate defi ciency, mimicking thrombotic thrombocytopenic purpura (TTP). Case presentationA 47-year-old male was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
0
0
2
Order By: Relevance
“…Segundo Lavriša et al, (2022) a Vitamina B12 ou cobalamina tem importante função para manutenção do metabolismo celular, atuando como cofator de processos metabólicos, como na síntese de DNA e no funcionamento mitocondrial. Ademais, a deficiência de ácido fólico, também torna a eritropoiese ineficaz devido à síntese prejudicada do DNA e à maturação celular (LEE et al, 2020). A deficiência dessas vitaminas, geralmente se deve à ingestão dietética inadequada, mas também pode se originar de má absorção intestinal, falhas no metabolismo de folato, aumento das necessidades durante a gravidez ou alcoolismo crônico (NDIAYE et al, 2017).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Segundo Lavriša et al, (2022) a Vitamina B12 ou cobalamina tem importante função para manutenção do metabolismo celular, atuando como cofator de processos metabólicos, como na síntese de DNA e no funcionamento mitocondrial. Ademais, a deficiência de ácido fólico, também torna a eritropoiese ineficaz devido à síntese prejudicada do DNA e à maturação celular (LEE et al, 2020). A deficiência dessas vitaminas, geralmente se deve à ingestão dietética inadequada, mas também pode se originar de má absorção intestinal, falhas no metabolismo de folato, aumento das necessidades durante a gravidez ou alcoolismo crônico (NDIAYE et al, 2017).…”
Section: Resultsunclassified
“…Enquanto países subdesenvolvidos, como o Paquistão, e que não apresentam nenhuma lei ou decreto que obrigue a indústria alimentícia a acrescentar ácido fólico em determinados alimentos como farinha e arroz, apresentam maiores níveis de anemia por deficiência de vitamina B9. A Europa, apesar de ser um continente majoritariamente desenvolvido, optou pela fortificação voluntária, apresentando números maiores de casos de anemia em comparação aos países que optaram pela fortificação obrigatória (GODOY e TABARES, 2018; SOOFI et al, 2017).deficiência de folato e na doença renal, mas o ácido metilmalônico não, tornando-se um marcador mais específico de deficiência de vitamina B12(LEE et al, 2020).Em relação ao tratamento, ocorre a administração em pequenas doses de ácido fólico e vitamina B12 todos os dias para enfermos que não possuam deficiência grave ou acometimentos neurológicos. Uma suplementação com altas doses por via oral pode ser absorvida, mesmo na ausência de fator intrínseco.…”
unclassified
“…Any sort of interruption in these procedures could result in ineffective haematopoiesis and accumulation of homocysteine. Homocysteine in excessive quantity is a toxic compound which could cause oxidative stress and inflammation in the blood vessels 22 .…”
Section: Discussionmentioning
confidence: 99%
“…A few patients had a history of gastrectomy and alcoholism as comorbidities. Harada et al [ 26 ] reported a history of gastric cancer, and Lee et al [ 35 ] reported a history of lymphoma.…”
Section: Reviewmentioning
confidence: 99%
“…Chang et al reported celiac disease as a possible etiology [ 19 ]. One case each of autoimmune gastritis, Helicobacter pylori , and atrophic gastritis etiologies was reported [ 35 , 43 , 51 ]. Other rare etiologies included gastric resection [ 26 ] and bowel resection [ 41 ].…”
Section: Reviewmentioning
confidence: 99%